Sistem Pakar Mendiagnosa Gizi Buruk pada Anak dengan Metode Dempster-Shafer - Ismail Ismail; Yesika Syarif; Muh. Idris (Pusat Riset dan Inovasi Nasional, 2026)
Diagnostic of nutritional status and detection of malnutrition of children at an early stage is crucial in the process of children growth. However, parents often assume their child nutritional status without doctor or experts consult as well as many older people who have limited knowledge of nutrition issues. Malnutrition must immediately treated, because if its too late perform actions treatment can lead to the death. An expert system is a computer-based system that uses knowledge, facts and reasoning techniques to solve problems that typically can only be solved by an expert in a particular field. The use of this expert system will be easier when implemented into a web-based application, besides computers and the Internet are already widely held by most people, it also can be accessed through mobile device with the internet and mobile browser accessed anywhere and anytime. In this research the type of malnutrition that can be detected as many as three kinds using the Dempster-Shafer method with symptoms based on users input. This expert system is implemented using the PHP programming language integrated with the MySQL database. The test using a validation testing (black box testing) and testing the accuracy of expert systems. The result of the validation test is 100% which indicates that the functionality of the system can run well appropriate with the list of requirements. The result of the accuracy testing is 75% which indicates that the expert system can function reasonably well in according to the Dempster-Shafer methods.